A look at elevator charateristics and basis values - Pommer, Paul (Kansas State University, 2013)
The agricultural commodity market has been experiencing previously unseen high prices in recent years. This new era of prices brings with it new challenges within agriculture for farmers and grain buyers within agriculture. This research explores the basis values of hard red winter wheat in Kansas and the elevator characteristics that provide a competitive advantage for elevators buying wheat in Kansas. This research explores hard red winter wheat basis values from elevators located around Kansas from 2002 to 2013. Two hundred twenty eight locations from around Kansas were used in the research. These locations provided the price data that was used for this research. The elevator characteristics used in the research were collected from the Kansas Grain and Feed Directory and the Burlington Northern-Santa Fe and Union Pacific railway companies. Five elevator characteristics were researched that may have a significant impact on an elevators basis. These characteristics are thought to provide a competitive advantage to the location in the form of stronger or narrower basis bids to the farmer, giving the farmer a higher price for his grain. The characteristics researched included elevator capacity, transportation capabilities, elevator terminal status, shuttle loading status, and cooperative or investor-owned business structure. Each characteristic was compared against their counterpart. For example, a location is either a shuttle loader or it is not. The research provides grain companies and farmers some data that they may find useful in marketing grain and setting basis levels in the ever changing and volatile market place in today’s grain industry.
Keywords: Basis; Wheat; Elevator; Future prices; Cash prices; Shuttle loader; Agriculture, General (0473); Economics, Agricultural (0503)